SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMA BANTUAN OPERASIONAL PENYELENGARAAN (BOP) PAUD (PENDIDIKAN ANAK USIA DINI) MENERAPKAN METODE ELECTRE (STUDI KASUS : DINAS PENDIDIKAN KABUPATEN SIMALUNGUN) - Sianturi, Putri; Mesran, Mesran; Ramadhani, Putri; Al-Hafiz, Nofri Wandi (STMIK Budi Darma, 2017)
Early Childhood Education (PAUD) is one of the government programs in guidance aimed at children from birth up to the age of six that is done through the provision of education to support the growth and development of physical and spiritual so that children have readiness in entering further education. The application of ELECTRE (Elimination And Choice Translation Reality) is aimed at selecting PAUDs eligible for government assistance. Determination of policies taken as the basis for decision-making must use criteria that can be clearly and objectively defined.